Greenhouse gas emissions of amusement parks in Taiwan. (July 2017) - Wang, Jen Chun; Wang, Yi-Chieh; Ko, Li; Wang, Jen Hsing
Abstract: This study investigated the greenhouse gas emissions of amusement parks in Taiwan. The energy use of 26 parks evenly distributed throughout Taiwan was audited. An average of 583, 000 people was found to visit each site annually. In addition, average annual energy consumption of 7699 MW h per site was observed, translating into 4096 t of carbon emissions per year. Every visitor generated an average of US29.4 in revenue and 7.4 kg-CO2 eq. The parks offering luxury services, such as 4-or 5-star accommodation and luxury food products, or many large-scale motorized water- or ground-based attractions consumed more energy than did ecology- and education-oriented parks. We categorized the parks into five categories, and found significant discrepancies among them in energy use. Two models for predicting annual carbon emissions and average carbon emissions per visit were developed, with the adjusted coefficient of determination being 0.934 and 0.792. This paper concludes by proposing several guidelines to assist park operators in reducing carbon emissions and improving energy efficiency.